Genetic factors and the risk of drug-resistant epilepsy in young children with epilepsy and neurodevelopment disability: A prospective study and updated meta-analysis. Issue 12 (26th March 2021) - Lin, Chien-Heng; Chou, I-Ching; Hong, Syuan-Yu
Abstract : Abstract: Drug-resistant epilepsy (DRE) affects 7% to 20% of children with epilepsy. Although some risk factors for DRE have been identified, the results have not been consistent. Moreover, data regarding the risk factors for epilepsy and its seizure outcome in the first 2 years of life are limited. We analyzed data for children aged 0 to 2 years with epilepsy and neurodevelopmental disability from January, 2013, through December, 2017. These patients were followed up to compare the risk of DRE in patients with genetic defect (genetic group) with that without genetic defect (nongenetic group). Additionally, we conducted a meta-analysis to identify the pooled prevalence of genetic factors in children with DRE. A total of 96 patients were enrolled. A total of 68 patients were enrolled in the nongenetic group, whereas 28 patients were enrolled in the genetic group. The overall DRE risk in the genetic group was 6.5 times (95% confidence interval [CI], 2.15–19.6; p = 0.03) higher than that in the nongenetic group. Separately, a total of 1308 DRE patients were participated in the meta-analysis. The pooled prevalence of these patients with genetic factors was 22.8% (95% CI 17.4–29.3). The genetic defect plays a crucial role in the development of DRE in younger children with epilepsy and neurodevelopmental disability. The results can serve as a reference for further studies of epilepsy panel design and may also assist in the development of improved treatments and prevention strategies for DRE.